Climate change mitigation projections for ASEAN - Rasiah R.; Al-Amin A.Q.; Chowdhurry A.H.; Ahmed F.; Zhang C. (Routledge, 2023)
ASEAN; carbon emission; climate change; climate effect; emission control; environmental economics; Gross Domestic Product; modeling